Analisis Sikap Siswa terhadap Kemampuan Pemecahan Masalah Matematis - Hella Jusra; Luthfiyah Aulia Iskandar (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This study aims to identify the attitudes of students on the ability to solve problems with mathematics. The attitudes of students evaluated in this study include self-confidence, anxiety, enthusiasm, and self-regulated mathematics learning. The research subjects were 79 students in grade VIII. The researcher re-concentrated on three students from all of them, who had mathematical problem-solving skills in the high, medium, and low groups. These subjects were selected from students who focused on problem-solving mathematical skills, questionnaires on the attitudes of students, and interviews with researchers. The instruments used to collect were an instrument of problem-solving mathematical ability and an instrument of students’ attitudes in the form of student attitudes towards mathematics questionnaire. The research method used is descriptive qualitative. The findings have shown that the majority of students are balanced between excited and unexcited on mathematics. The majority reason for students who are enthusiastic about mathematics is that they can improve their abilities, talents, and knowledge. Others have different explanations such as having the resources; formulas and problems, making them feel challenged; thinking that mathematics is important. The majority of students had a low category of self-confidence and anxiety towards mathematics, and had a moderate level of enthusiasm in mathematics and self-regulated learning.